Perceptions of women enrolled in a cardiovascular disease screening and prevention in HIV study - Sherika Hanley; Galaletsang J. Ndlazi; Stacy T. Maddocks; Verusia Chetty (South African Family Practice)
Background: The ISCHeMiA (integration of cardiovascular disease screening and prevention in the human immunodeficiency virus [HIV] management plan for women of reproductive age) study is an ongoing, 3-year, prospective, quasi-experimental study comparing usual care to a primary health care intervention plan guided by the World Health Organization Package of Essential Non-Communicable (WHO-PEN) disease interventions. Sixty eight percent of women were overweight or obese at baseline in the ISCHeMiA study, many of whom reported nonadherence to interventions at 6 months post enrolment. This study explores the perceptions of women living with HIV (WHIV) towards their participation in the ISCHeMiA study to understand the barriers and facilitators to lifestyle modification interventions for cardiovascular disease (CVD) risk prevention.